Plasma haemoxygenase-1 in coronary artery disease - Idriss, Naglaa K.; Lip, Gregory Y. H.; Balakrishnan, Balu; Jaumdally, Rumi; Boos, Christopher J.; Blann, Andrew D. (Thrombosis and Haemostasis, 2010)
It was the aim of this study to determine plasma haemoxygenase-1 (HO-1) across the spectrum of health, angina but normal coronary arteries (NCA), stable coronary artery disease (CAD), and acute coronary syndromes (ACS), and relationships with angiogenin, matrix metalloproteinase-9 (MMP-9), tissue inhibitor of metalloproteinase-1, and vascular endothelial growth factor. Plasma markers were measured (ELISA) in peripheral venous citrated plasma from 50 healthy subjects, 30 with NCA, 70 with stable CAD and 24 with an ACS, and from patient’s aortic root, coronary ostium, coronary sinus and femoral artery. Human umbilical vein endothelial cells (HUVECs) were cultured with or without tumour necrosis factor (TNF), and platelets were probed. HO-1 was raised in stable CAD (p<0.05) and increased further in ACS (p<0.01) compared to healthy controls and NCA. HO-1 correlated only with MMP-9, and then only in the healthy controls. There were no major differences from cardiac or peripheral sites. HO-1 was present in HUVECs and 24-hour HUVEC supernatants but release was abolished by TNF. Platelets had no HO-1. In conclusion, HO-1 is raised in stable CAD and ACS and may arise from the endothelium but not the platelet. This may have implications for our understanding of the pathophysiology of CAD and its acute presentation as ACS.
Keywords: Haemoxygenase-1; angiogenin; matrix metalloproteinase-9; tissue inhibitor of metalloproteinase; vascular endothelial growth factor; coronary artery disease